Oxazole Analogues as Potential Therapeutic Agents: A Comprehensive Review - Goel, Neetu; Mudgil, Sarwan; Kasnia, Rishabh; Demiwal, Sunaina; Nehra, Bhupender (Pharmaceutical Fronts, 2025)
Oxazole, a five-membered heterocyclic motif composed of three carbon atoms, one oxygen atom, and one nitrogen atom with one carbon atom between the oxygen and nitrogen atoms, has attained remarkable notice in medicinal chemistry because of its diverse and potent biological effects. The unique structural features of oxazole make it a valuable scaffold for the generation of novel therapeutic agents. Over the years, oxazole derivatives have demonstrated a wide range of therapeutic actions, including anti-inflammatory, antitumor, antidepressant, analgesic, antidiabetic, diuretic, antibacterial, and anticonvulsant effects. These biological activities make them promising candidates for the treatment of various diseases. As a result, there has been an increasing interest in synthesizing new oxazole-based compounds with enhanced efficacy and selectivity for therapeutic applications. The present review aimed to provide a comprehensive overview of the chemical characteristics of oxazole and its congeners, highlighting their biological roles and potential for drug development. In addition, structure–activity relationship analysis explored the key substituents that favor the pharmacological potential against a range of clinical disorders. By consolidating current knowledge on the therapeutic potential of oxazole, this review seeks to stimulate further research and innovation in the pharmaceutical industry, material science, and academia, with the goal of addressing unmet medical needs.
Keywords: oxazole; antibacterial; anticancer; anti-inflammatory; analgesic